Towards the mutual recognition of sacraments between the Orthodox Church and the Catholic Church - Marek Blaza (Ephata)
The main task in this research is to find the solution for bilateral recognition of sacraments between the Catholic Church and the Orthodox Church. The former one recognises the validity of all sacraments administered in the non-Catholic Eastern Churches because they have apostolic succession. In Catholic theology, a sacrament can exist when it is properly administered, according to the teaching of St Augustine: “The Word accedes to the element and becomes a sacrament”. The above criteria are also used by some local Orthodox Churches, which recognise the validity of the baptism of non-Orthodox Christians. Not all local Orthodox Churches recognise baptism administered by non-Orthodox Christians. For these local Orthodox Churches the criterion is the maxim of St Cyprian of Carthage “Outside the Church there is no salvation”. It means that there can be no sacrament outside the visible boundaries of the Orthodox Church. In order to present these two different conceptions of the theology of the sacraments (St Cyprian’s and St Augustine’s), the definition of a sacrament and the question of the number of sacraments will first be presented. And then there will be given a proposal to change the legal terminology to theological terminology.